Radiological and Clinical Findings of Multiple Cerebellar Liponeurocytoma: A Case Report - Wang, Shan; Xu, Xiaopei; Wang, Chao (Frontiers in Surgery, 2021)
Background: Cerebellar liponeurocytoma is an extremely rare benign tumor which generally occurs in cerebellum and is almost always solitary. Multifocal cerebellar liponeurocytoma is exceedingly rare, only 8 cases has been reported so far. Herein we present the 9th case of multifocal cerebellar liponeurocytoma in a 70-year-old woman with the complete clinical course and comprehensive imaging findings. Case Presentation: A 70-year-old woman presented with a history of intermittent headache for 5 years. Computed tomography (CT) and magnetic resonance imaging (MRI) of the brain have been performed and suggested a diagnosis of teratoma based on the imaging findings. After the surgical resection of the lesion, histopathological and immunohistochemical analyses revealed neuronal, glial, and lipomatous components and confirmed the diagnosis of multifocal cerebellar liponeurocytoma after surgical resection. During the 2-year follow-up period, the patient showed no signs of recurrence or metastasis. Conclusion: We described the radiological characteristics and clinical course of an exceedingly rare case of multifocal cerebellar liponeurocytoma in the cerebellar vermis and temporal lobe. The clear multifocality makes this case unusual.